Antibiotic resistance bacteria and genes fate and transport in aquatic environments: advancing water quality models development - Jampani, Mahesh; Mateo-Sagasta, Javier (2025)
Antibiotics have revolutionized modern medicine, saving millions of lives; however, antibiotic misuse and overuse have led to antibiotic resistance (AR). While AR research has traditionally focused on human and animal health within the One Health spectrum, in recent years, the importance of the environment in AR dissemination is gaining attention. Water quality modeling is necessary to understand the propagation of antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs), and their associated health risks. Our research aims to identify knowledge gaps and research priorities for developing water quality models for assessing the fate and transport of ARB and ARGs. We performed an extensive review and analysis of model development in both AR and water quality, and present conceptual frameworks for water quality modeling that provide inputs for predictive model development and guiding risk assessments of AR transmission and spread in aquatic environments. This research offers critical insights for developing predictive models through a detailed review of methods and approaches, which can be used to evaluate antibiotics, ARB and ARGs that enter aquatic environments from various sources. While some processes related to ARB and ARG growth or decay in water environments are well understood, many others remain unclear. Current microbial fate and transport models can be enhanced with new rates and parameters; however, the development of additional modules, such as gene transfer influencing bacterial resistance, is imperative. Sophisticated models must incorporate complex hydrological, climatic, and ecological factors and processes that govern the development of resistance. Future research should focus on developing water quality model modules to address antibiotic drug resistance and estimate disease burden. Investing in robust modeling frameworks is crucial for managing environmental pollution, mitigating health risks associated with AR, and ensuring the safety and sustainability of the natural environment within a One Health approach.